2016
DOI: 10.1039/c6ew00007j
|View full text |Cite
|
Sign up to set email alerts
|

A survey of indicator parameters to monitor regrowth in unchlorinated drinking water

Abstract: The objective of our study was to explore microbiological parameters that are suitable as indicators for regrowth in distribution systems that receive unchlorinated drinking water in the Netherlands. Treated water and distributed water at two locations in the distribution system of 28 treatment plants were analyzed for a range of biological parameters. The results demonstrated that Aeromonas, HPCs, and Mycobacterium were significantly (more often) higher and ATP was significantly (more often) lower in the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Members of this genus are known symbionts in ant fungal gardens, where they help establish a monoclonal fungal garden by expressing antibiotic compounds that avoid the proliferation of a pathogenic fungus . Possible fungal–prokaryote symbioses cannot be excluded, as several studies have already reported the presence of fungi in all sorts of drinking water. , Furthermore, the presence of Actinobacteria possibly excreting antimicrobial compounds might offer an explanation for the relatively low biodiversity and richness observed in the biofilm and small loose deposits of DWDS#2 (, Supporting Information, Figure S8, pdf) and again may be linked to lower regrowth associated issues at this location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of this genus are known symbionts in ant fungal gardens, where they help establish a monoclonal fungal garden by expressing antibiotic compounds that avoid the proliferation of a pathogenic fungus . Possible fungal–prokaryote symbioses cannot be excluded, as several studies have already reported the presence of fungi in all sorts of drinking water. , Furthermore, the presence of Actinobacteria possibly excreting antimicrobial compounds might offer an explanation for the relatively low biodiversity and richness observed in the biofilm and small loose deposits of DWDS#2 (, Supporting Information, Figure S8, pdf) and again may be linked to lower regrowth associated issues at this location.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, heterotrophic plate counts (HPC) and sometimes additional single regrowth indicator species (e.g., aeromonads in The Netherlands) are included in legislative routine monitoring of distributed drinking water quality. , However, these culture-dependent methods do not give any insights into the complete microbial community composition and spatial–temporal changes within DWDSs, which are dynamic ecosystems . Culture-dependent surveys typically cover the fast-growing, opportunistic bacteria, which are unlikely to be the representative abundant or functionally relevant species in such oligotrophic environments.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of bacterial richness during distribution may be associated with regrowth, particularly in large distribution systems where bulk water is transported over long distances. Microbial growth in drinking water has been observed in the form of higher particle counts and increased turbidity (Liu et al, 2016), higher cell counts (Hammes et al, 2008) and increase in the presence of indicator organisms in the final tap water compared to the water leaving the treatment plant (van der Wielen et al, 2016). The water leaving the treatment plant may therefore be impacted by the distribution system itself through processes such as pipe corrosion (Sun et al, 2014), the detachment of biofilms (Chaves Simões and Simões, 2013) and suspension of loose deposits (Liu et al, 2013;Liu et al, 2017;Liu et al, 2018).…”
Section: The Interplay Between Spatial and Temporal Dynamics Of The Dwdsmentioning
confidence: 99%
“…According to Gasol and Del Giorgio, these results indicated that the HNA group could be an active group of heterotrophic bacteria [34]. In previous studies, the HPC was found to be a better indicator of microbial regrowth than TCC [35]. Herein, the average HPC of the influent water was 1368 CFU/mL, and in the BAC columns, 56%, 68%, 61%, and 66% of the HPCs was removed in the control, nutrient-enhanced, oxidant-enhanced, and nutrient + oxidant-enhanced columns, respectively.…”
Section: Microbial Characterizationmentioning
confidence: 79%